Effect of Seaweed Concentrates on the Growth and Biochemical Constituents of - A.B. Sabale2, N.M. Pise1* and (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-ansi-language: EN-US; mso-bidi-font-family: ’Times New Roman’; mso-bidi-language: AR-SA;">Effect of seaweed extract on growth and biochemical constituents of fenugreek was investigated using Ulva fasciata, Sargassum ilicifolium and Gracilaria corticata compared with the Hoagland nutrient medium. Fresh, dried and boiled extracts of Ulva, Sargassum and Gracilaria influenced photosynthetic pigments percentage in fenugreek in similar way as did Hoagland nutrition medium. Shoot growth and fresh biomass recorded at 50% SWC was comparable to that observed with the Hoagland solution and notably significant when compared to the control plants. Carbohydrate, proteins, free amino acids, polyphenols and nitrogen content also increased in seaweed treated plants. Extract of Ulva was found slightly more effective than that of Sargassum and Gracilaria.<span style="font-size: 10.5pt; line-height: 110%; font-family: ";Times New Roman";,";serif";; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">